Thermal Annealing Effect on Structural, Morphological, and Sensor Performance of PANI-Ag-Fe Based Electrochemical E. coli Sensor for Environmental Monitoring. (20th May 2015) - Mohammad Naim, Norshafadzila; Abdullah, H.; Umar, Akrajas Ali; Abdul Hamid, Aidil; Shaari, Sahbudin
Abstract : PANI-Ag-Fe nanocomposite thin films based electrochemical E. coli sensor was developed with thermal annealing. PANI-Ag-Fe nanocomposite thin films were prepared by oxidative polymerization of aniline and the reduction process of Ag-Fe bimetallic compound with the presence of nitric acid and PVA. The films were deposited on glass substrate using spin-coating technique before they were annealed at 300°C. The films were characterized using XRD, UV-Vis spectroscopy, and FESEM to study the structural and morphological properties. The electrochemical sensor performance was conducted using I-V measurement electrochemical impedance spectroscopy (EIS). The sensitivity upon the presence of E. coli was measured in clean water and E. coli solution. From XRD analysis, the crystallite sizes were found to become larger for the samples after annealing. UV-Vis absorption bands for samples before and after annealing show maximum absorbance peaks at around 422 nm–424 nm and 426 nm–464 nm, respectively. FESEM images show the diameter size for nanospherical Ag-Fe alloy particles increases after annealing. The sensor performance of PANI-Ag-Fe nanocomposite thin films upon E. coli cells in liquid medium indicates the sensitivity increases after annealing.